Hardening Tor Hidden Services - Tippe, Pascal (My University, 2023)
Tor is an overlay anonymization network that provides anonymity for clients surfing the web but also allows hosting anonymous services called hidden services. These enable whistleblowers and political activists to express their opinion and resist censorship. Administrating a hidden service is not trivial and requires extensive knowledge because Tor uses a comprehensive protocol and relies on volunteers. Meanwhile, attackers can spend significant resources to decloak them. This thesis aims to improve the security of hidden services by providing practical guidelines and a theoretical architecture. First, vulnerabilities specific to hidden services are analyzed by conducting an academic literature review. To model realistic real-world attackers, court documents are analyzed to determine their procedures. Both literature reviews classify the identified vulnerabilities into general categories. Afterward, a risk assessment process is introduced, and existing risks for hidden services and their operators are determined. The main contributions of this thesis are practical guidelines for hidden service operators and a theoretical architecture. The former provides operators with a good overview of practices to mitigate attacks. The latter is a comprehensive infrastructure that significantly increases the security of hidden services and alleviates problems in the Tor protocol. Afterward, limitations and the transfer into practice are analyzed. Finally, future research possibilities are determined.
Keywords: Hardening Tor Hidden Services, Hardening Tor Onion Services, Vulnerabilities Hidden Services, Security Architecture Hidden Services, Deanonymizing Hidden Services, Hidden Service, Onion Services